2(5x+2)=-2(5x-5)-3x

Simple and best practice solution for 2(5x+2)=-2(5x-5)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5x+2)=-2(5x-5)-3x equation:



2(5x+2)=-2(5x-5)-3x
We move all terms to the left:
2(5x+2)-(-2(5x-5)-3x)=0
We multiply parentheses
10x-(-2(5x-5)-3x)+4=0
We calculate terms in parentheses: -(-2(5x-5)-3x), so:
-2(5x-5)-3x
We add all the numbers together, and all the variables
-3x-2(5x-5)
We multiply parentheses
-3x-10x+10
We add all the numbers together, and all the variables
-13x+10
Back to the equation:
-(-13x+10)
We get rid of parentheses
10x+13x-10+4=0
We add all the numbers together, and all the variables
23x-6=0
We move all terms containing x to the left, all other terms to the right
23x=6
x=6/23
x=6/23

See similar equations:

| 6x^2-8x+1=x+4 | | 2(3x+1)=7(2+x) | | )-3(x-5))/5=(3(-2x+1))/4 | | 58-10k=3k-6 | | P(x)=X^3-x-5 | | 2x+9+36-x=13x-5 | | 12t-10=14t | | 14=5v-2v | | –q=7+6q | | -700+15x=1000 | | 14=5v=2v | | 4x+6=15x-27 | | –q=7+6qq= | | 700+15x=1000 | | 8x-7+9x=15+7x | | x2+8x=-6 | | 3x2+17x+22=0 | | 7+2s=s-8+12 | | 4(5x+90)=2(x+72) | | -2/5w-5/3=7/3w-1 | | 100+100+80+d=360 | | 0=x6 | | 2(v+3)=-2(6v-1)+2v | | 1/3(x+28)=4/5x | | -x^3=343 | | 4x²+2x-12=0 | | 2(y+1)=6y-34 | | -x3=343 | | 16a=180 | | 6.x2-4x+27=0 | | 17-20z=-13-18z | | 3(2x-3)=4x-1 |

Equations solver categories